ZAKAT PRODUKTIF DAN PERANNYA TERHADAP PERKEMBANGAN UMKM (Studi pada LAZ el-Zawa UIN Maulana Malik Ibrahim, Malang) - Khairani Miftahul; Marlina Ekawaty (Jurnal Ilmiah Akuntansi & Bisnis, 2017)
This paper aims to know the distribution of zakat funds, both consumptive and productive, and the role of productive zakat to the development of micro-enterprise mustahik LAZ el-Zawa UIN Maliki, Malang. Descriptive and multiple regression analyzes were used against primary data collected by interviewing the LAZ board and distributing questionnaires to beneficiaries of zakat funds (mustahik) LAZ el-Zawa. The results show that the zakat fund collected is channeled for consumptive purposes in the form of scholarships, old-age charitable donations, and charity. While the form of channeling of funds for productive purposes is the provision of business capital loans with qardul hasan UMKM and mudharabah UMKM programs. In the meantime, this study found that the amount of productive zakah earned mustahik significantly influence the development of the mustahik business. Likewise, the variable length of business and gender, but the frequency attendance in coaching and age have an insignificant effect. LAZ el-Zawa needs to increase the amount of productive zakat distributed to mustahik so that the micro enterprise mustahik increase, so gradually they can switch the role is no longer as mustahik but muzakki, that is people who pay zakat. Thus productive zakat can reduce the number of poor people.Keywords: Medium, small and micro-enterprises; el-Zawa, Productive zakat